An insight and update on the analgesic properties of vitamin C - Nallan CSK Chaitanya; Arvind Muthukrishnan; CMS Krishnaprasad; Gali Sanjuprasanna; Poojaragini Pillay; Balmoori Mounika (Wolters Kluwer Medknow Publications, 2018)
Pain is an unpleasant subjective feeling having implications on both physical and mental realm. Multiple dimensions of pain involving behavioral, spiritual, emotional, and cognitive changes have been studied and pathways elucidated. It is stressed that the nature in which pain is modulated and perceived at a higher center is a complex phenomenon. One of the main goals of pain modulation is to modify pain to a more tolerable level, rather than its complete eradication. Different pain management interventions were tried but have effects that are more adverse. Till date, the only reliable pain blockers are analgesics and anti-inflammatory drugs in the form of opioids and non-opioids. Despite this, most of the drugs are ineffective at various levels, furthermore, adding to complications. Thus, there is an urgent need for effective intervention with minimal side effects. Ascorbic acid, popularly known as vitamin C, has shown to exhibit promising analgesic properties. The literature is sparse with the usage of the drug in various forms of pain. This review focuses on the dynamics and kinetics of vitamin C and its usage in various forms of pain. With minimal adverse effects, the drug is shown to perform well in different types of pain disorders, thus paving way for alternative interventional agent for pain management.